CLIPA7 Exhibits Pleiotropic Roles in the Anopheles gambiae Immune Response - Renée Zakhia; Mike A. Osta (Karger Publishers, 2022)
Clip domain serine proteases and clip domain serine protease homologs (cSPHs) are key components of serine protease cascades that drive the melanization response. Despite lacking catalytic activity, cSPHs play essential roles in regulating melanization, but the spectrum of functions they catalyze within and outside these cascades is not fully understood. Aside from their classical role as cofactors for PPO activation, we have previously revealed an unprecedented complexity in the function and molecular organization of these cSPHs in the immune response of the malaria vector Anopheles gambiae. Here, we add yet another dimension to the complex roles underpinning the contributions of cSPHs to mosquito immunity by showing that CLIPA7, a member of the expanded cSPH family, defines a novel branch within the cSPH network that is essential for the melanization of Escherichia coli but not Plasmodium ookinetes or Gram-positive bacteria. Despite its dispensability for the melanization of Gram-positive bacteria, we show that CLIPA7 is required for the clearance of systemic infections with Staphylococcus aureus. CLIPA7 is produced by hemocytes and associates with the surfaces of live E. coli and S. aureus cells in vivo as well as with those of melanized cells. Based on its RNAi phenotypes and its unique domain architecture among A. gambiae cSPHs including the presence of an RGD motif, we propose that CLIPA7 exhibits pleiotropic roles in mosquito immunity that extend beyond the regulation of melanization to microbial clearance.